2018
DOI: 10.1177/0095399718760587
|View full text |Cite
|
Sign up to set email alerts
|

Double Standards in Frontline Decision Making: A Theoretical and Empirical Exploration

Abstract: Drawing on status characteristics and double standards theory, this study explores how social categories may affect the standards tax officials use in evaluating citizen-clients’ trustworthiness, leading to differential evaluation. Whereas the street-level bureaucracy literature mainly focuses on the direct effect of social categories on officials’ judgments, this study shows how stereotyping in the public encounter could be much subtler and more pervasive than is hitherto studied. Based on semistructured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Studies have documented SLBs' trust in their clients being very relevant to the formers' decisions (Yang and Holzer 2006). Furthermore, various elements such as honesty (Maynard-Moody and Musheno 2003), trustworthiness (Raaphorst and Groeneveld 2018), and cooperativeness (Maynard-Moody and Leland 2000) play a significant role in how SLBs evaluate their clients' level of deservingness. Trust is a major factor in SLBs' assessment of clients' 'worthiness' (Yang 2005).…”
Section: Trust In the Context Of Street-level Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented SLBs' trust in their clients being very relevant to the formers' decisions (Yang and Holzer 2006). Furthermore, various elements such as honesty (Maynard-Moody and Musheno 2003), trustworthiness (Raaphorst and Groeneveld 2018), and cooperativeness (Maynard-Moody and Leland 2000) play a significant role in how SLBs evaluate their clients' level of deservingness. Trust is a major factor in SLBs' assessment of clients' 'worthiness' (Yang 2005).…”
Section: Trust In the Context Of Street-level Workmentioning
confidence: 99%
“…Recent studies demonstrate that SLBs may make differing decisions based on how they assess their clients' moral characteristics. For example, they may divide their clients into stereotypical categories (Raaphorst and Groeneveld 2018) that help them evaluate clients' level of 'deservingness' (Jilke and Tummers 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas digital templates could be experienced as useful "reminders," they could thus also be seen as diverting attention away from "real problems" (Checkland, McDonald, and Harrison 2007). Research has shown that street-level bureaucrats prefer information assessed in face-to-face interactions with citizen-clients over information generated by digital systems (Raaphorst and Groeneveld 2018). Looking specifically at the NHS case, we have seen that physicians, who can be depicted as professionals having "strong discretion," perceive a digital system as less useful, and feel threatened, when it codifies knowledge that previously belonged to their professional discretion.…”
Section: Power and Discretionmentioning
confidence: 99%
“…Next to recent works on discrimination or stereotyping (e.g. Jilke & Tummers, 2018; Raaphorst & Groeneveld, 2018), street‐level bureaucracy (SLB) research has diagnosed (Maynard‐Moody & Musheno, 2000) and documented (e.g. Tummers, 2017; Tummers & Bekkers, 2014) the tension between two ‘narratives’ of frontline work.…”
Section: Introductionmentioning
confidence: 99%
“…employment or welfare: Dias & Maynard‐Moody, 2007; Tummers & Bekkers, 2014), on regulatory services (e.g. tax, food or building inspectors: de Boer & Eshuis, 2018; May & Wood, 2003; Raaphorst & Groeneveld, 2018) or police services (e.g., Epp, Maynard‐Moody, & Haider‐Markel, 2014; Maynard‐Moody & Musheno, 2003). However, the lack of studies conducted in correctional settings remains paradoxical as Lipsky argues that the correction field provides a ‘highly refined example of street‐level bureaucratic discretion’ (Lipsky, 2010, p. 13).…”
Section: Introductionmentioning
confidence: 99%